Selection of personal medical and health insurance company by using Fuzzy TOPSIS / Nur Ain Qamarina Zulkifly, Zurina Kasim and Jasmani Bidin - Zulkifly, Nur Ain Qamarina; Kasim, Zurina; Bidin, Jasmani (Universiti Teknologi MARA, Perlis, 2019)
There are many types of insurance offered by various number of companies. Medical and health insurance especially, has become a necessity today due to the expensive hospital bills and medical cost. Each company offers various type of packages for the customer to choose from. As a costumer, to make a decision on the selection of the right insurance company based on several criteria is quite challenging. Therefore, this study aims to help the customer in choosing suitable personal medical and health insurance by comparing 4 insurance companies based on 4 criteria. The evaluation from experts on each criterion against each alternative using linguistic variables were collected. The evaluation seem to have uncertainty and subjectivity. Therefore, this research used Fuzzy Techniques for Order Preference by Similarity to Ideal Situation (TOPSIS) method to rank the insurance companies since it is able to deal with the uncertainty and subjectivity of the data. The finding shows that Prudential holds the highest rank, followed by AiA, Great Eastern and Zurich.